Association of Vitamin D Deficiency with Early Onset of Osteoarthritis - Rasheed, Nusrat; Makhdoom, Asadullah; Khan, Muhammad Shafiq; Rasheed, Naseem; Khan, Muhammad Hassan (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To evaluate the association of serum vitamin D deficiency and early onset of osteoarthritis (OA) knee joints. Methodology: This single-blinded comparative OPD based study, conducted at Dow University Hospital, Karachi. Patients <40 years of age having knee pain for the last six months were included. Osteoarthritis was classified according to the Kellgren Lawrence(KL) scale. Randomization was done, dividing the patients in two groups. One with normal vitamin D level whereas the other group had low levels of vitamin D. Both groups were compared based on X-ray findings to evaluate the association of OA with vitamin D deficiency. RESULTS: In our study, out of 152 patients, 106 were diagnosed with Osteoarthritis. The mean age was 36.84 years. Serum calcium level normal in 100 (65.8%) patients. Based on radiological findings, 75 (49.3%) were KL grade 1 while 31 (20.4%) were grade 2, 75 (49.3%) had right-sided knee involvement. In the group with low levels of serum vitaminD, 32 (40%) had right knee affected, 25 (31.3%) had left, 20 (25%) had bilateral knee involvement, whereas three had normal knee joints The Chi-square test showeda positive relationship between low levels of vitamin D and osteoarthritis. Conclusion: The above study shows statisticaly significant association between vitamin D deficiency and early onset of osteoarthritis. Cartilage loss and radiographic progression of the disease are important factors to understand the disesease pathogienesis. Therapeutic or preventive role of vitamin D in osteoarthritis may be established but for that long term studies are needed. Keywords: Osteoarthritis, Vitamin D, Kellgren Lawrence scale, BMI.